406. COMPARISON OF OUTCOMES BETWEEN SALVAGE OESOPHAGECTOMY AFTER DEFINITIVE CHEMORADIOTHERAPY WITH PLANNED OESOPHAGECTOMY AFTER NEOADJUVANT CHEMORADIOTHERAPY. (24th September 2022) - Cooper, Scott; Frankel, Adam; Thomson, Iain; Thomas, Janine; Smithers, Mark
Abstract: Definitive chemoradiotherapy (dCRT) for oesophageal cancer is recommended in selected patients who are unfit for surgery, or where doctor and/or patient prefers to surgery. Salvage oesophagectomy after dCRT is reportedly a morbid procedure compared to oesophagectomy following neoadjuvant chemoradiotherapy (nCRT). If indications for dCRT expand, there will be a larger pool of patients requiring salvage oesophagectomy. We aimed to assess the post-operative clinical outcomes of patients who had dCRT compared with nCRT in our unit. Data were obtained from a prospectively maintained database of patients receiving curative treatment for oesophageal cancer from January 2010 until February 2022. Patients receiving a salvage oesophagectomy after dCRT were compared to those receiving nCRT and planned oesophagectomy. An comparison of differences in group characteristics, post-operative outcomes and survival rates was made. Analysis was completed using t-test, chi-square, log rank and Kaplan–Meier methods. 216 patients had dCRT with 24 undergoing salvage oesophagectomy. 228 had nCRT followed by surgery. The salvage group had more SCC (47% versus 16%; p = 0.002), higher blood loss (434 versus 280 mL; p = 0.033) and more surgeon-rated technical problems (e.g. pleural adhesions or mediastinal fibrosis) (30% versus 11%; p = 0.010). Operative times were not significantly different (357 versus 330 minutes; p = 0.232). There was a trend towards higher complications in the dCRT group (83 versus 63%; p = 0.057). Operative mortality was 0% in both groups. As expected the median survival was worse in the dCRT group (26 versus 66 months; p = 0.040). Patients selected to dCRT who require and are fit for salvage oesophagectomy have worse outcomes compared with those who have nCRT. However, this subgroup still have a modest potential for cancer survival. Our dataset adds to the existing literature and will help to counsel patients being considered for salvage oesophagectomy. The possible future increase in number of patients being offered dCRT makes improving the understanding of peri-operative and cancer-specific outcomes after salvage oesophagectomy a priority.